Новый вид кровососущего мокреца (Diptera, Ceratopogonidae) из Степи Украины - Шевченко, А.К. (Вестник зоологии, 1970)
Описывается новый вид кровососущего мокреца — Cuculicoides stanicicus Shevtshenk o sp. п. Его голотип (препарат № 22) хранится в коллекции Института зоологии АН УССР под номером IN 1/1. The new species — Culicoides stanicicus Shevtshenko sp. n. is described. Ils holotype (preparation No 22) is maintained in the collection of the Institute of Zoology of the Academy of Sciences of the Ukrainian SSR (No IN 1/1).